US Valuation of the SF-6D. (August 2013) - Craig, Benjamin M.; Pickard, A. Simon; Stolk, Elly; Brazier, John E.
Background. The original SF-6D valuation study collected 3503 standard gambled responses from 611 UK respondents to predict quality-adjusted life year (QALY) values.Methods. Using 19, 980 paired comparison responses from 666 US respondents and a stacked probit model, the 25 coefficients of the original SF-6D multiattribute utility (MAU) regression were estimated, such that each coefficient represents a QALY decrement. The US QALY predictions were compared with UK predictions using 8428 SF-6D states in the US Medicare Health Outcomes Survey (MHOS), 1998 to 2003.Results. Twenty-two of the 25 decrements in the SF-6D MAU regression are statistically significant. The remaining decrements are insignificant based on US and UK results. The US and UK QALY predictions for the MHOS SF-6D states are remarkably similar given differences in experimental design, format, and sampling (Lin's coefficient of agreement, 0.941; absolute mean difference, 0.043).Limitations. The underlying theoretical framework for the study design and econometric analysis builds from the episodic random utility model and the concept of QALYs and inherits their limitations.Conclusions. This study enhances the potential for US comparative effectiveness research by translating SF-6D states into US QALYs as well as improves upon discrete choice experiment design and econometric methods for health valuation.